Perspective article: Actions to reconfigure food systems - Loboguerrero Rodriguez, Ana María; Thornton, Philip K.; Wadsworth, Jonathan; Campbell, Bruce M.; Herrero, Mario; Mason-D'Croz, Daniel; Dinesh, Dhanush; Huyer, Sophia; Jarvis, Andy; Millan, Alberto; Wollenberg, Eva Karoline; Zebiak, Stephen E. (Elsevier, 2020)
There is broad agreement that current food systems are not on a sustainable trajectory that will enable us to reach the Sustainable Development Goals by 2030, particularly in the face of anthropogenic climate change. Guided by a consideration of some food system reconfigurations in the past, we outline an agenda of work around four action areas: rerouting old systems into new trajectories; reducing risks; minimising the environmental footprint of food systems; and realigning the enablers of change needed to make new food systems function. Here we highlight food systems levers that, along with activities within these four action areas, may shift food systems towards more sustainable, inclusive, healthy and climate-resilient futures. These actions, summarised here, are presented in extended form in a report of an international initiative involving hundreds of stakeholders for reconfiguring food systems.